Processo educativo: sociedade e natureza. As Geociencias como vetor no processo educativo - Barcelos, J. H. (My University, 1994)
This paper presents methodological questions and new ideas related to the Geosciences concepts and its development in association to the Natural Sciences study for Elementary and Basic Schools. Special attention has been focused to the NIMEC', a project responsible for programs to the Natural Sciences progress and global information in the Environmental Education. The geologic environment relationships constitute the demarcator that includes some Environmental Education matter. Interdisciplinary focus seems to be the most adequate way to the necessary community participation. -English summary
Educational process: society and nature. Geosciences as an educational process vector
Keywords: elementary school; environmental education; geological education